USE OF WEARABLE TECHNOLOGIES IN HEALTH PROMOTION IN HUMAN MEDICINE STUDENTS - YLLACONZA, JAVIER EDUARDO CURO (2024)
INTRODUCTION: IN THE CURRENT ERA MARKED BY RAPID TECHNOLOGICAL ADVANCES, THE INTEGRATION OF WEARABLE DEVICES INTO EVERYDAY LIFE HAS BEEN A REMARKABLE PHENOMENON. THESE DEVICES, RANGING FROM SMART WATCHES TO PHYSICAL ACTIVITY MONITORS, HAVE GAINED POPULARITY AND HAVE BECOME UBIQUITOUS TOOLS THAT TRACK VARIOUS ASPECTS OF HEALTH AND WELLNESS. OBJECTIVE: TO CHARACTERIZE THE USE OF WEARABLE TECHNOLOGIES IN HEALTH PROMOTION IN HUMAN MEDICINE STUDENTS. METHODS: THE RESEARCH IS CHARACTERIZED BY ITS CROSS-SECTIONAL AND QUANTITATIVE NATURE, WITH A BASIC AND DESCRIPTIVE NON-EXPERIMENTAL DESIGN. THE STUDY POPULATION CONSISTED OF 128 STUDENTS OF HUMAN MEDICINE AT A PRIVATE UNIVERSITY LOCATED IN AREQUIPA, PERU. DATA COLLECTION WAS CARRIED OUT THROUGH THE USE OF SURVEYS AND QUESTIONNAIRES. RESULTS: REGARDING THE ADOPTION AND USE OF WEARABLE TECHNOLOGIES, 35.94% (46) REPORTED A MODERATE LEVEL, 32.81% (42) INDICATED A HIGH LEVEL, WHILE 31.25% (40) INDICATED A LOW LEVEL. THIS FINDING SUGGESTS A BALANCED AND NON-EXTREME ADOPTION OF WEARABLE TECHNOLOGIES AMONG THE STUDENTS EXAMINED IN THE CONTEXT OF HEALTH PROMOTION. CONCLUSIONS: WE WERE ABLE TO DETERMINE A MODERATE LEVEL OF ADOPTION AND USE OF WEARABLE TECHNOLOGIES AMONG HUMAN MEDICINE STUDENTS TO PROMOTE HEALTH AND WELLNESS. THIS RESULT POINTS TO THE RELEVANCE OF THESE TECHNOLOGIES IN HEALTH-RELATED ACTIVITIES, HIGHLIGHTING A PARTICULAR EMPHASIS ON A MODERATE LEVEL OF USE. © 2024 YLLACONZAET AL., LICENSED TO EAI.